The gene panel with methylation-related genes and clinical factors for predicting overall survival of endometrial cancer: Risk factors for prognosis of EC - Jiao, Lijuan; Li, Junyan; Ma, Jiong; Cheng, Pu; Pang, Yue (Journal of Medical Biochemistry, 2025)
Background: This study aimed to identify novel methylation-based prognostic biomarkers for endometrial cancer (EC) to facilitate early diagnosis and treatment. To explore methylation-related prognostic markers in endometrial tissue by analyzing TCGA data and to establish a methylation-based risk model for EC patients.Materials and Methods: We systematically analyzed methylation-related gene expression and prognostic significance in 409 EC patients using TCGA DNA methylation data. DNA methylation biomarkers were identified through consensus clustering and weighted gene co-expression network analysis (WGCNA). The clusterProfiler algorithm was employed to determine key signaling pathways across different subgroups. A gene panel targeting critical DNA methylation sites was subsequently constructed.Results: A methylation-related prognostic risk model was developed, incorporating five CpG sites: cg01416891, cg00082235, cg01493517, cg03811891, and cg05317207. The model demonstrated strong predictive performance, with high-risk patients exhibiting significantly poorer prognoses compared to low-risk patients. A gene panel was also established to predict prognosis across different EC risk groups.Conclusion: The methylation-related gene panel model serves as a reliable prognostic biomarker for EC, offering potential for enhanced early diagnosis and personalized treatment strategies.